Interfacial structure and strengthening mechanisms of NiO-coated graphene reinforced aluminum matrix composites - Xin Gao; Dong Ai; Jiahao Zhang; Hongyan Yue; Xiaohua Zhang; Chunyu Zhang; Zhongkai Zhang; Jing Chang (Journal of Materials Research and Technology)
The interfacial bonding between graphene and Al critically influences the composite's strengthening efficiency. In this paper, nickel oxide nanoparticle-coated reduced graphene oxide (NiO@rGO) reinforcements were synthesized by alcohol-thermal and annealing process. Subsequently, NiO@rGO/Al composites were fabricated through intermittent ball milling and hot-press sintering. The presence of NiO leads to a thermite reaction during the high-temperature sintering process, forming a distinctive graded interface structure of graphene/Al2O3/Al, which boosts the interface bonding strength and enhances the load-transfer ability. Concurrently, the thermal effect generated by the Al thermal reaction would facilitate the long-distance diffusion of Ni atoms, contributing to the generation of intragranular Al3Ni, which avoids premature fracture due to stress concentration at the interface. Consequently, the composite demonstrates excellent mechanical properties. Compared to pure Al, the composite's ultimate tensile strength has increased by 66% (143.1 ± 2.3 MPa). Theoretical modeling analysis indicates that the primary enhancements in the NiO@rGO/Al composite material stem from load transfer and interface thermal mismatch.